Analisis Pengungkapan Key Audit Matters dalam Laporan Tahunan Perusahaan Konstruksi dan Bangunan Indonesia Tahun 2022-2023 - Hidayat, Andika Rahman; Cheisviyanny, Charoline (Universitas Negeri Padang, 2025)
This study analyzes the disclosure of Key Audit Matters (KAM) in the annual reports of construction and building companies listed on the Indonesia Stock Exchange for 2022-2023. KAMs highlight significant audit aspects requiring detailed auditor explanations. The research identifies trends and frequencies in KAM disclosures and explores influencing factors. Findings show revenue recognition is a frequent KAM issue in the Indonesian construction sector due to the complexity of measuring and recording revenue from long-term projects, which involve significant estimates and assessments. The implementation of PSAK 72, governing revenue recognition from contracts with customers, has further emphasized revenue as a KAM. Additionally, trade receivables are commonly disclosed due to high credit risk and uncertainty in collection, impacting cash flow. KAM disclosures regarding receivables provide transparent information about asset quality and associated risks. This research enhances theories related to KAM disclosure practices and enriches academic literature in accounting and auditing. The findings aim to boost investor confidence in the Indonesian capital market, especially in the construction sector, by highlighting the importance of transparency in financial reporting to improve information quality for stakeholders.